Uplink traffic scheduling with QoS support in broadband wireless access networks - Tang, Sze Yin; Chieng, David; Chang, Yoong Choon (2009)
With the ever-growing demand for multimedia applications over broadband wireless access networks, an efficient traffic scheduler is deemed crucial for the provision of quality-of-service (QoS). A large number of traffic scheduler schemes have been proposed, and those equipped with channel-aware capability appear to be most promising. These schedulers are capable of exploiting the dynamic channel condition and traffic characteristics in order to improve the channel utilization and guarantee QoS. Nevertheless, there is still lack of clarity amongst the existing channel-aware schemes on which is the most suitable to support multiple traffic classes with diverse QoS requirements. Furthermore, the majority of existing traffic scheduling works focus on the downlink direction, hence this motivates us to study for the uplink case. In this paper, we compare the performance of the most promising scheme, namely, the modified largest weighted delay first (M-LWDF) scheduling algorithm against other representative traffic scheduling algorithms, i.e., weighted round robin (WRR), max-sum-capacity (MSC) and proportional fair (PF). We also discuss the effectiveness of each algorithm in meeting the desired QoS requirements.